In situ synthesized BSA capped gold nanoparticles: effective carrier of anticancer drug methotrexate to MCF-7 breast cancer cells - Murawala, Priyanka; Tirmale, Amruta; Shiras, Anjali; Bhagavatula L. V. Prasad (Materials Science & Engineering C-Materials For Biological Applications, 2014)
The proficiency of MTX loaded BSA capped gold nanoparticles (Au-BSA-MTX) in inhibiting the proliferation of breast cancer cells MCF-7 as compared to the free drug Methotrexate (MTX) is demonstrated based on MTT and Ki-67 proliferation assays. In addition, DNA ladder gel electrophoresis studies, flow cytometry and TUNEL assay confirmed the induction of apoptosis by MTX and Au-BSA-MTX in MCF-7 cells. Notably, Au-BSA-MTX: was found to have higher cytotoxicity on MCF-7 cells compared with an equivalent dose of free MTX. The enhanced activity is attributed to the preferential uptake of Au-BSA-MTX particles by MCF-7 cells due to the presence of BSA that acts as a source of nutrient and energy to the rapidly proliferating MCF-7 cells. Moreover, the targeting ability of the drug MTX to the over expressed folate receptors on MCF-7 cells also contributes to the enhanced uptake and activity. Taken together, these results unveil that Au-BSA-MTX could be more effective than free drug for cancer treatment. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Apoptosis; Bovine serum albumin; Cancer therapy; Cytotoxicity; Dual active agents; gold nanoparticles